Silver-promoted solid-phase guanidinylation enables the first synthesis of arginine glycosylated Samoamide A cyclopeptide analogue - Liang, Bingxin; Li, Rong; Li, Linji; Tang, Ming; Li, Xiang; Su, Chunli; Liao, Hongli (Frontiers in Chemistry, 2023)
Cyclization and glycosylation serve as effective approaches for enhancing the drug properties of peptides. Distinct from typical glycosylation, atypical arginine N-glycosylation has drawn increasing attention due to its fundamental role in various cellular procedures and signaling pathways. We previously developed a robust strategy for constructing arginine N-glycosylated peptides characterized by silver-promoted solid-phase guanidinylation. Modeled after cyclic octapeptide Samoamide A, an antitumor peptide composed of eight hydrophobic amino acids extracted from cyanobacteria, herein we first performed arginine scanning to determine an optimal position for replacement with arginine. Consequently, the first synthesis of arginine glycosylated Samoamide A cyclopeptide analogue was described combining solid-phase glycosylation with solution-phase cyclization. The resultant SA-HH-TT displayed enhanced water solubility compared with the non-glycosylated SA-HH-TT. Notably, our method provides a universal strategy for synthesizing arginine N-glycosylated cyclopeptides.